Analisis Performa PID, Fuzzy-PID, dan Model Predictive Control (MPC) untuk Pengaturan Ketinggian Air Bendungan - Muhamad Zia Ulhaq; Desmira Desmira; Miftakhul Azamah; Imratul Nazifah; Meisya Dwi Rizkiana; Yoga Angga Pratama (Teknik: Jurnal Ilmu Teknik dan Informatika, 2026)
This study analyzes the performance of three types of controllers—PID, Fuzzy-PID, and Model Predictive Control (MPC)—in maintaining water level stability in a dam system. Proper water level regulation is essential to prevent flooding, ensure adequate water distribution, and maintain the structural safety of the dam. Previous studies have widely implemented PID and Fuzzy-PID controllers; however, MPC offers significant advantages through system prediction and multivariable optimization. This research compares the performance of the three controllers through simulation analysis using a second-order mathematical model. The results indicate that MPC has the potential to deliver a faster settling time and a smaller steady-state error compared to PID and Fuzzy-PID, although it requires higher computational complexity.